Effect of neurally adjusted ventilator assist versus pressure support ventilation on asynchronies and cardiac function in pediatric liver transplantation - Fabrizio Chiusolo; Giorgia Spinazzola; Roberta Costa; Alessio Franceschini; Francesca Tortora; Francesco Polisca; Emanuele Rossetti; Lucilla Ravà; Marcello Chinali; Vito Fanelli; Giorgio Conti (Scientific Reports)
Abstract In pediatric liver recipients perioperative factors may affect respiratory and cardiac function, and prolong mechanical ventilation during post-operative period. The use of NAVA can improve the interaction between the patient and the ventilator from both a respiratory and cardiac perspective. The objective of this study is to evaluate the synchronization between the patient and the ventilator, as well as cardiac function, during the application of neurally adjusted ventilatory assist (NAVA) and pressure support ventilation (PSV) in pediatric liver transplant recipients. This is a single-center, prospective, randomized, physiological cross-over controlled trial conducted between 2021 and 2022. Children (1 month-10 years old) who underwent liver transplantation were admitted to the pediatric intensive care unit. Patients were randomised to one of two crossover sequences of ventilation trials of 40 min each (PSV/NAVA/PSV or NAVA/PSV/NAVA). Cardiac function was studied by echocardiogram. Twenty-four patients were enrolled and 21 completed the study. Primary outcomes were variation of asynchrony index (AI) and tricuspid annular plane systolic excursion (TAPSE) during the two ventilation modes. Secondary outcomes were patient-ventilator interaction parameters, gas exchange, left and right ventricular function, and hemodynamic parameters. NAVA compared to PSV: (1) improves patient-ventilator interaction reducing AI (coeff − 6.66 95% CI −11.5 to −1.78, p = 0.008); (2) does not improve TAPSE (coeff 0.62 95% CI −1.49 to 2.74, p < 0.557) No differences in terms of pulmonary gas exchange and hemodynamic parameters were detected. NAVA (when compared to PSV) improves patient-ventilator interaction in terms of asynchronies without affecting cardiac biventricular function. Trial registration: NCT 04792788, Registration date: 2021-03-11.